THE BALLOT OR THE BULLET - A Speech of Malcom X - Z. Zakaria (Universitas Sembilanbelas November Kolaka, 2016)
Indeed, this article focus on one of speech of Malcolm X related to political thought and idea that how to throw away the prejudice and racial discrimination of white people, so whites could live as equal as black in the United States. Malcolm mentioned that under the control of white hegemony, and also because black people had not given their liberation from whites, it was true if blacks legalized their actions (by necessary means) in getting their rights. They legalized whatever means to throw away the white racism for reaching their freedom, and whatever means will do in getting the goal. That’s the Malcolm, by necessary means come into the struggle for gaining black’s liberation, equality, and human justice in the United States. The final tendentious action of Malcolm is to come into political action; he tended to get the political ways rather than separation in solving the race problem in the United States. For Malcolm, integration and fight for getting the rights of vote was the moderate ways in gaining the black common humanity (freedom, equality, and human justice) because they were supported by the principles of Charter of the United Nation, the Universal Declaration of Human rights, and the Constitutional of the U.S.A. This article was conducted by interdisciplinary approaches; historical, sociological, political, biographical and literary approaching.